EFFECT OF SWEET FLAG RHIZOME, ACORUS CALAMUS L. FORMULATIONS AGAINST SITOPHILUS ORYZAE IN SORGHUM - H. C. LATHA; A. NAGANAGOUD (The Bioscan, 2015)
Investigation were conducted to test the insecticidal activity of sweet flag rhizome (Acorus calamus L.) formulations against Sitophilus oryzae on sorghum in storage during 2012-13 and 2013-14 at the Department of Agricultural Entomology, College of Agriculture, Raichur, Karnataka state. The results revealed that the sweet flag rhizome powder with talc as a carrier at two per cent concentration reduced the seed damage to 35.67 per cent as against 98.67 per cent in untreated check after 120 days of treatment (DAT), among the different carriers in the experiment the best carrier with reduced seed damage was observed in talc (4.00%) at 30 DAT and the efficacy continued even upto 120 DAT (40.33%) during 2012-13 while the least performance was noticed when wood ash was used as carrier at 30 DAT (20.33%) and also at 120 DAT (86.00%). The trend remained same in the subsequent year of the experimentation.With respect to weight loss, seeds treated with sweet flag rhizome powder along with talc as carrier at two percent as it recorded 2.50 per cent seed weight loss after 120 days and highest weight loss was recorded in the seeds treated with wood ash (27.05) at 120 DAT during 2012-13 and 2013-14 pooled. The number of adults emerged per 100g of seeds after 120 days of treatment was minimum (59.17 adults/100 g of seeds) in seeds treated with sweet flag rhizome powder with talc as a carrier at two per cent concentration. Overall the study concludes that use of sweet flag rhizome powder is effective in reducing the damage with talc as the effective carrier.